THE EFFECT OF ENVIRONMENTAL, SOCIAL AND GOVERNANCE (ESG) PRACTICES AND SAFETY ON FINANCIAL PERFORMANCE - Kashmala Mukhtiar; Dr. Anjum Ihsan; Dr. Shahid Jan Kakakhel (International Journal of Contemporary Issues in Social Sciences, 2024)
ESG and Organizational Safety have become an area of major concerns for the firms considering their financial performance as stakeholders are demanding the incorporation of ESG & Safety dimensions in the firms’ operations. Furthermore, this study investigate the Sample of the study consists of top 100 firms based on the market capitalization firms, listed on the Pakistan Stock Exchange. Secondary data were collected related to variables of the study. Moreover, content analysis was employed to measure the ESG & Safety dimension, Financial Performance. Descriptive statistics were used to describe the characteristics of each individual variable followed by the correlation analysis to ascertain the association among the variables. Finally, the regression analysis was applied to determine the dependency of ROA (firm financial performance) on the independent variables. Findings of the study indicate the significant positive effect of ESG & Safety on the firm financial performance. The control variables also demonstrated the positive and significant effect on the firm financial performance.